Does managing the consumption of people with severe alcohol dependence reduce harm? A comparison of participants in six Canadian managed alcohol programs with locally recruited controls - Stockwell, Tim; Pauly, B.; Chow, C.; Erickson, R.; Krysowaty, B.; Roemer, A.; Vallance, K.; Wettlaufer, A.; Zhao, J. (Wiley-Blackwell Publishing Ltd., 2017)
© 2017 Australasian Professional Society on Alcohol and other Drugs (APSAD). Introduction and Aims: Managed alcohol programs (MAP) are intended for people with severe alcohol-related problems and unstable housing. We investigated whether MAP participation was associated with changes in drinking patterns and related harms. Design and Methods: One hundred and seventy-five MAP participants from five Canadian cities (Hamilton, Ottawa, Toronto, Thunder Bay and Vancouver) and 189 same-city controls were assessed for alcohol consumption, health, safety and harm outcomes. Length of stay in a MAP was investigated as a predictor of drinking patterns, non-beverage alcohol consumption and related harms. Statistical controls were included for housing stability, age, gender, ethnic background and city of residence. Negative binomial regression and logistic regression models were used. Results: Recently admitted MAP participants (=2months) and controls were both high consumers of alcohol, predominantly male, of similar ethnic background, similarly represented across the five cities and equally alcohol dependent (mean Severity of Alcohol Dependence Questionnaire=29.7 and 31.4). After controlling for ethnicity, age, sex, city and housing stability, long-term MAP residents ( > 2months) drank significantly more days (+5.5) but 7.1 standard drinks fewer per drinking day than did controls over the last 30days. Long-term MAP residents reported significantly fewer alcohol-related harms in the domains of health, safety, social, legal and withdrawal. Discussion and Conclusions: Participation in a MAP was associated with more frequent drinking at lower quantities per day. Participation was associated with reduced alcohol-related harms over the past 30days. Future analyses will examine outcomes longitudinally through follow-up interviews, police and health care records.